De la situation particulière des professeurs d'administration en contexte universitaire - Turmel, Andre (Canadian Journal of Higher Education, 1986)
The purpose of this text shall be to analyse the representations scientists entertain about their research. These representations are grasped mainly through discus-sions researchers hold about their profession. Elaboration of scientific policy is accompanied by intense reflexive work which is in reality a narration of ongoing research experiences. How do scientists speak about research? To what type of knowledge do they refer when they speak of their scientific work? Scientific policy is a rationalisation of the research policy and this rationalisation brings about an understanding of the social logic underlying research. In fact the logic of spatialisation is confronted with the logic of temporality, the moment in the process of setting up the space-time relationship in any research.